Contact Pressure Distribution on Subgrade Soil Underlying Geocell Reinforced Foundation Beds - Dash, Sujit Kumar; Saikia, Rupam; Nimbalkar, Sanjay (Frontiers in Built Environment, 2019)
High contact stresses generated in the foundation soil, owing to increased load, causes distress, instability and large settlements. Geocell reinforcement is being widely used for the performance improvement of foundation beds. Pressure distribution on subgrade soil in geocell reinforced foundation beds is studied through model tests and numerical analysis. The test data indicates that with provision of geocell reinforcement the contact pressure on the subgrade soil reduces significantly. Consequently, the subgrade soil tends to remain intact until large loadings on the foundation leading to significant performance improvement. Through numerical analysis it is observed that the geocells in the region under the footing were subjected to compression and beyond were in tension. This indicates that the geocell reinforcement right under the footing directly sustains the footing loading through mobilisation of its compressive stiffness and bending rigidity. Whereas, the end portions of the geocell reinforcement, contribute to the performance improvement in a secondary manner through mobilisation of anchorage derived from soil passive resistance and friction.